Transformation of Teacher Evaluation in Improving the Quality of Community-Based Madrasah Education - Bariroh, Umi; Salafudin, Moh Anwar; Muhammadi, Qasem (QUALITY, 2025)
AbstractThis study aims to evaluate the implementation of teacher performance assessment in improving the quality of education in community-based madrasah ibtidaiyah. A descriptive qualitative approach was used through a case study at MI NU 09 Kauman Boja Kendal. The informants consisted of 16 teachers and 1 madrasah head who were selected purposively. Data were collected through in-depth interviews, observations, and documentation, and then analyzed using thematic techniques. The results of the study show that the implementation of teacher performance assessment is still administrative, unsustainable, and has less impact on improving the quality of learning. Senior teachers with civil servant status and a service period of more than 15 years show a low level of participation in the evaluation process due to the lack of follow-up and professional strengthening. Other inhibiting factors include low digital literacy, lack of learning innovation, and an organizational culture that is less open to feedback. This study recommends strengthening reflective supervision and the formation of professional learning communities based on the principles of total quality management as a strategy for sustainable teacher performance improvement.